"Learning from my experience": Acute abdomen - Perforated Meckel's diverticulitis. (2019) - Brackett, William Janika; Khullar-Gupta, Shikha
Highlights: Acute surgical abdomen has a limited differential in pediatric population. Meckel's diverticulum can mimic the clinical findings of acute appendicitis. Careful radiographic review to identify the appendix in the pediatric population with acute abdomen. Surgical pathology of a normal appendix and a perforated Meckel's Diverticulitis, with a retrospective view of the appendix. Abstract: This is a case report documenting the risk in imaging misinterpretation of a pediatric patient that presented with an acute abdomen. Computed Tomography (CT) demonstrated an inflamed blind ending loop of bowel in the pelvis without an obvious cecal connection. The patient was taken to the operative theater, a normal appendix and perforated Meckel's diverticulitis were resected. Meckel's diverticulum is the most common small bowel abnormality and can have complications. We will emphasize that imaging studies in a pediatric patient with Meckel's diverticulum are easily subject to errors radiologists make. This is such a cautionary and learning tale.